Medical mycology in the United States a historical analysis (1894-1996) - Espinel-Ingroff, Ana (Kluwer Academic Publishers, 2003)
The development of medical mycology in the United States is assessed within the context of scientific progress as demonstrated by the creativity and scholarly contributions from research, technological activities, and training toward the management of fungal diseases. Although it focuses on American figures and events, it covers the origins of the discipline in Europe and Latin America. It describes historically significant scientific, technological and educational development and the narrative description is accompanied by an analysis of the causes of these and their perceived impact on the development of the discipline from the late 1880s into the 1990s. The development was conceptualised into five eras: "the era of discovery", "the formative years", "the advent of antifungal and immunosuppressive therapies", "the years of expansion" and "the era of transition".